NAVIGATING ECONOMIC TIDES: ASSESSING THE IMPACT OF EXPORTS, EXCHANGE RATES, AND CORRUPTION ON INDONESIA'S FOREIGN EXCHANGE RESERVES - Whinarko Juli Prijanto; Bagus Adhi Laksono (Jurnal REP (Riset Ekonomi Pembangunan), 2023)
One indicator that reflects the stability of the economy in a country is foreign exchange reserves. Foreign exchange reserves serve as the savings and accumulation of a country's income over a specific period. This research study is conducted with the aim of elucidating the phenomena and the impact of exports, exchange rates, and corruption on foreign exchange reserves. The ECM model analysis is employed because it is suitable for the type of data used, namely time series data from 1998 to 2022. The results of this research indicate that, from a long-term perspective, the main factors influencing foreign exchange reserves are exports and corruption, while in the short term, exports and exchange rates are the primary factors affecting foreign exchange reserves.